2021
DOI: 10.1016/j.ijppaw.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

High winter loads of Oestrid larvae and Elaphostrongylus rangiferi are associated with emaciation in wild reindeer calves

Abstract: The Oestrid flies Cephemyia trompe and Hypoderma tarandi and the nematode Elaphostrongylus rangiferi are important parasites of Rangifer spp. The larvae of Oestrid flies develop in the throat ( C. trompe ) and skin ( H. tarandi ) of their host during winter while E. rangiferi develop in the CNS. Oestrid pupation, and development of E. rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Ideally, the bone marrow fat index should be used in combination with visual fat assessment of the carcass. This has also been the conclusion in other studies that evaluated measures of body condition in reindeer [45,49].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Ideally, the bone marrow fat index should be used in combination with visual fat assessment of the carcass. This has also been the conclusion in other studies that evaluated measures of body condition in reindeer [45,49].…”
Section: Discussionsupporting
confidence: 80%
“…Handeland et al (2021) found that high number/load of the three parasites Cephenemyia trompe, Hypoderma tarandi and Elaphostrongylus rangiferi in wild reindeer in uenced the body condition in calves and increased the risk of emaciation [49]. However, the mean load/range of these parasites were much higher than those seen in our results.…”
Section: Discussioncontrasting
confidence: 72%
“…The seNorge mean daily temperature dataset, and other seNorge products, have been used in a variety of studies (e.g. Erlandsen et al, 2021;Belušić et al, 2020;Handeland et al, 2021;Lawrence, 2020).…”
Section: Nwp Systemmentioning
confidence: 99%
“…(2018; 2019) for details. The seNorge mean daily temperature dataset, and other seNorge products, have been used in a variety of studies (e.g., Belušić et al ., 2020; Lawrence, 2020; Erlandsen et al ., 2021; Handeland et al ., 2021). In our study, they are used as a proxy for local, observed surface temperatures.…”
Section: Data Productsmentioning
confidence: 99%